Extraction And Identification Of Elastase Inhibitory Peptides From Digested Ovalbumin As Skin Anti-Aging Therapeutics Agent - Chok, Wen Xin (Universiti Sains Malaysia, 2020)
This research was aimed to produce elastase inhibitor peptides from ovalbumin (main protein in egg white) using enzymatic (i.e. pepsin, trypsin and chymotrypsin) hydrolysis approach, to identify the inhibitor peptides using liquid chromatography tandem mass spectrometry integrated with Bioinformatics approach, and to investigate the structural activity relationship between the selected inhibitor peptides and elastase.